2011
DOI: 10.1039/c1cc13328d
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole-modified porphyrin as a pH-responsive sensitizer for cancer photodynamic therapy

Abstract: 5,10,15,20-Tetrakis(N-(2-(1H-imidazol-4-yl)ethyl)benzamide)porphyrin produced twice as many singlet oxygen ((1)O(2)) molecules at pH 5.0 (quantum yield 0.53 ± 0.01) than at pH 7.4, whereas the (1)O(2) quenching rate was reduced by a factor of 2.5 for a pH change from 7.4 to 5.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…QDots are small semiconductor NPs that possess several exciting features such as high photostability, narrow and tunable emission spectra and high brightness [17]. Owing to these properties, QDots have shown great potential for many biomedical applications, including cell labeling applications [18][19][20][21], long-term tracking of (single) molecules [22], in vivo imaging [23,24] and photodynamic therapy [25,26]. However, despite their excellent photophysical properties, their toxicity, in particular due to the release of Cd 2+ ions [27,28], remains an issue of debate [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…QDots are small semiconductor NPs that possess several exciting features such as high photostability, narrow and tunable emission spectra and high brightness [17]. Owing to these properties, QDots have shown great potential for many biomedical applications, including cell labeling applications [18][19][20][21], long-term tracking of (single) molecules [22], in vivo imaging [23,24] and photodynamic therapy [25,26]. However, despite their excellent photophysical properties, their toxicity, in particular due to the release of Cd 2+ ions [27,28], remains an issue of debate [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…For high‐tumor‐specific damage and imaging, low pH‐induced activation is key. An imidazole‐modified porphyrin as a low‐pH‐activatable porphyrin has been reported . This system is extremely interesting; however, the ratio of the photosensitization efficiency in the ON state to that in the OFF state is not sufficiently high.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work showed that imidazole-modified porphyrin, 5,10,15,20-tetrakis(N-(2-(1H-imidazol-4-yl)ethyl)benzamide)porphyrin, produced twice as many 1 O 2 molecules at pH 5.0 than at pH 7.4, whereas 1 O 2 quenching rate was reduced by a factor of 2.5 for a pH change from 7.4 to 5.0. 20 Imidazole moieties were employed as a pH-sensitive trigger for controllable 1 O 2 release. Wang, Zhang and co-workers prepared a pH-responsive nanoparticle-5 based platform for controllable 1 O 2 production where both hydrophobic porphyrin and pH-indicator bromocresol purple (BCP) were encapsulated in organically modified silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%